2011
DOI: 10.1037/a0022550
|View full text |Cite
|
Sign up to set email alerts
|

Functional disruption of the brain mechanism for reading: Effects of comorbidity and task difficulty among children with developmental learning problems.

Abstract: Objective The study investigated the relative degree and timing of cortical activation associated with phonological decoding in poor readers. Method Regional brain activity was assessed during performance of a pseudoword reading task and a less demanding, letter-sound naming task by three groups of students: children who experienced reading difficulties without attention problems (N = 50, RD) and nonreading impaired (NI) readers either with (N = 20) or without attention-deficit/hyperactivity disorder (ADHD; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 84 publications
(146 reference statements)
16
27
0
Order By: Relevance
“…C C C C C Gooch D, Snowling M, Hulme C (26) . PC C C C C Simos PG, Rezaie R, Fletcher JM, Juranek J, Passaro AD, Li Z et al (27) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…C C C C C Gooch D, Snowling M, Hulme C (26) . PC C C C C Simos PG, Rezaie R, Fletcher JM, Juranek J, Passaro AD, Li Z et al (27) .…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the second thematic axis, concerning studies that used both Speech-language Pathology and Neuropsychology assessments of ADHD, revealed 17 articles (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) , which assessed not only the Speech-language Pathology disorders observed in ADHD, but also the aspects related to neuropsychological performance, through specific tests and scales of evaluation of the disorder. Among the studies included in this theme axis, eight addressed reading difficulties (15,17,18,20,25,(28)(29)(30) ; two dealt with difficulties of math and reading (14,21) ; three had the relation between cerebral structures and the alterations of language as their main focus (16,19,27) ; one addressed neuropsychological performance in the inattentive and combined subtypes (24) ; one evaluated performance in executive and central coherence tasks (22) ; one focused on the perception of time, phonological skills, and executive function in ADHD (26) ; and one investigated fine motor, sensory and perceptual functions (23) .…”
Section: Analysis Of the Selected Studies According To The Proposed Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Students with dyslexia have also been shown to have some difficulties with executive functions such as planning, organizing and executing motor action, which contributes to reaching low performance in global motor activities (Simos et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This has been suggested that this may be related to shared genetics and also that in both cases problems are identified in cortical areas responsible for motor processing (motor planning and sequencing and preparation of movement) and cognitive aspects, such as attention (Cruddace & Riddell, 2006;Gabbard & Caçola, 2010;Zwicker, Missiuna, Harris, & Boyd, 2011;Martin, Piek, Baynam, Levy, & Hay, 2010;Capellini, Germano, & Padula, 2010;Simos et al, 2011;Hedenius et al, 2013).…”
Section: Introductionmentioning
confidence: 99%